1985
DOI: 10.1128/jcm.21.3.462-463.1985
|View full text |Cite
|
Sign up to set email alerts
|

Legionella oakridgensis: laboratory diagnosis of a human infection

Abstract: We report the laboratory diagnosis of a case of pneumonia caused by Legionella oakridgensis. L. oakidgensis, originally isolated from industrial cooling towers, has not previously been associated with human disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…lansingensis . These four species are also recognized as etiologic agents of Legionella infections (Tang et al. 1985; Wilkinson et al.…”
Section: Discussionmentioning
confidence: 99%
“…lansingensis . These four species are also recognized as etiologic agents of Legionella infections (Tang et al. 1985; Wilkinson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients had a previous history of immunological disorders treated with steroids (idiopathic thrombocytopenic purpura and rheumatoid arthritis, respectively), possibly rendering them more susceptible to infection. Pleural effusion was also present in the three previously reported cases of human L. oakridgensis infection (4,10,11), suggesting that this species might produce specific virulence factors (adhesins and/or extracellular products) favoring tropism for pleural tissue.…”
mentioning
confidence: 72%
“…L. oakridgensis was originally isolated from water in the environment (7,13) and was subsequently found to be responsible for several human cases of pleurisy (4,10,11). However, these human infections were diagnosed by DFA on clinical specimens and were not confirmed by culture of the organism (4, 10, 11).…”
mentioning
confidence: 99%
“…L. pneumophila, L. micdadei, L. sainhelense, L. bozemanii, and L. oakridgensis are the species of legionellae most frequently associated with HCA-LD. [11][12][13] In a review article in 2000, Yu 11 indicated that in an 18-month period there had been eight outbreaks of nosocomial LD and that cases were reported from long-term care facilities (LTCFs), rehabilitation centers, and pediatric hospitals as well as acute care hospitals. He indicated that contamination of the institutional water supply was consistently linked to these cases and that the role of contaminated cooling towers as a vector for LD was controversial, with only two such outbreaks since 1982, one of which was subsequently shown to be due to contaminated potable water.…”
Section: Biology and Reservoirs Of Legionella Speciesmentioning
confidence: 99%